2012
DOI: 10.1371/journal.pone.0036144
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Escherichia coli O157:H7 Clone Causing a Major Hemolytic Uremic Syndrome Outbreak in China

Abstract: An Escherichia coli O157:H7 outbreak in China in 1999 caused 177 deaths due to hemolytic uremic syndrome. Sixteen outbreak associated isolates were found to belong to a new clone, sequence type 96 (ST96), based on multilocus sequence typing of 15 housekeeping genes. Whole genome sequencing of an outbreak isolate, Xuzhou21, showed that the isolate is phylogenetically closely related to the Japan 1996 outbreak isolate Sakai, both of which share the most recent common ancestor with the US outbreak isolate EDL933.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 48 publications
(76 reference statements)
0
53
0
1
Order By: Relevance
“…Lineage I (LSPA-6 111111) has caused several outbreaks in Asia and the United States, including a major outbreak in 1999, which caused 177 deaths in Xuzhou, China (29). In the present study, a single LI isolate was found from a human case.…”
Section: Resultsmentioning
confidence: 55%
“…Lineage I (LSPA-6 111111) has caused several outbreaks in Asia and the United States, including a major outbreak in 1999, which caused 177 deaths in Xuzhou, China (29). In the present study, a single LI isolate was found from a human case.…”
Section: Resultsmentioning
confidence: 55%
“…A recent, multistate outbreak of Shiga toxin-producing EHEC O157:H7 infections that occurred in the US from April to June 2014 and was linked to ground beef, has caused an increased alarm on food safety. During 1999-2000, the Jiangsu, Anhui and Henan Provinces in China faced a massive outbreak of EHEC O157:H7 which caused 177 deaths due to hemolytic uremic syndrome [Xiong et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports associated with outbreaks of STEC around the world. In a massive outbreak in China, 195 hospitalised HUS patients and 177 deaths have been reported (Wang et al, 2011;Xiong et al, 2012). In another outbreak caused by non-O157 STEC, infected cases including 43 deaths have been recently reported in the European Union (ECDC, 2011).…”
Section: Introductionmentioning
confidence: 99%